Copper(II)‐Catalyzed Aerobic Oxidation of Amines: Divergent Reaction Pathways by Solvent Control to Imines and Nitriles. Issue 9 (16th July 2019) - Kim, Jihyeon; Golime, Gangadhararao; Kim, Hun Young; Oh, Kyungsoo
Abstract: The dehydrogenative coupling of amines by copper catalysts was investigated in the presence of molecular oxygen. By modulating the aerobic oxidation pathways of Cu(OAc)2 catalyst in different reaction solvents, the selective formations of homo‐coupled imines, cross‐coupled imines, and nitriles have been achieved from amine derivatives. The discovery of the multiple aerobic oxidation pathways of Cu(OAc)2 signifies the on demand reactivity control of the catalytically active copper species by the reaction solvents. Given that the aerobic oxidation protocols are of significant interest to the advancement of green chemical processes, the copper‐catalyzed aerobic oxidation reactions will be useful for a wide range of functional group transformations. Abstract : A divergent aerobic oxidation pathway of amines is accomplished by using different reaction solvents. The catalytic use of Cu(OAc)2 under molecular oxygen promoted the oxidation of amines to either imines or nitriles by simply changing the reaction solvent. The observed "on demand" aerobic oxidation pathways of amines should enrich our understanding of the copper catalyst system that can be further tuned for the enhanced reactivity and selectivity.